A Study of Inventory Theory - Geisler, Murray A. (Management Science, 1963)
The paper is divided along the following lines. First, I illustrate the inventory models having Deterministic Demand and then consider the class of Probabilistic Demand Models. Within the latter class, I consider the single period steady state case, and then the N-period dynamic inventory model. For the N-period case, I then report results covering non-zero procurement lead time, demand rate varying each period, joint solution of the inventory-control-production scheduling decision, and a multi-echelon model. Finally, since in the previous consideration of probabilistic demand models, knowledge of the demand probability distribution and its parameters were assumed, I discuss a paper dealing with the use of Bayes estimates.